Penerapan Teknologi Silase dan Fermentasi untuk Ketahanan Pakan Ternak di Daerah Sub-optimal Rejosari - Bantul - Susanti, Ari Diana; Cahyadi, Muhammad; Paryanto, Paryanto; Fadilah, Fadilah (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2021)
The availability of ruminant feed in terms of amount and nutritional adequacy is a common problem during the dry season. This condition is worst at the peak of the dry season (July - October) such as that faced by the Kelompok Tani Rukun Binantu of Rejosari in Bantul Regency - Yogyakarta. Pre-survey shows that the cost of feed in the dry season is uncompetitive to the price of cattle. This problem was solved by Program Kemitraan Masyarakat (PKM – UNS) 2020 with workshop in cattle feed preservation using silage and fermentation techniques. The silage technique is used in conventional-local forage, while the fermentation technique is aimed at preserving low-nutrient animal feed as well as improving digestibility and nutritional adequacy of the feed. Product’s monitoring and evaluation are carried out after 7 days for fermentation technique and 21 days for silage technique. The program is success in solving of Mitra’s problems and it is also one of Tri Dharma Perguruan Tinggi in technology transfer for rural communities.